Feeding and parasitism of adult Stenoperla spp. (Plecoptera: Eustheniidae) in New Zealand. Issue 2 (14th July 2016) - Winterbourn, Michael J; Pohe, Stephen R
Abstract: The adult diets of two species of stonefly, Stenoperla prasina (Newman, 1845) and Stenoperla maclellani Zwick, 1979 were investigated by gut content analysis. Adults were collected throughout New Zealand by light‐trapping at 77 streamside sites most of which were located in native forest. S. prasina was widely distributed and collected at 43 sites, whereas S. maclellani was sampled at 10 sites in the South Island only. Of 200 S. prasina and 42 S. maclellani dissected, 36% and 69% respectively, contained food. Microscopic examination of a subset of individuals indicated that the gut contents of both species were dominated by sooty mould fungi with lesser contributions made by plant tissue, pollen grains and the spores of tree ferns. These findings suggest that stoneflies had been feeding on the trunks, branches and foliage of trees and perhaps on fronds of tree ferns. As the abdomens of most females were packed with eggs, which mature in late‐instar nymphs it is likely that feeding provides adults with a source of immediately available energy for mating and flight. Encysted larval stages of hairworms (Nematomorpha) and a trematode were also found in both stonefly species. Metacercarial cysts of the trematode are the first records of larval flukes parasitising New Zealand stoneflies. They were found in about 43% of dissected adults of each species with up to 40 cysts present in some individuals. It is possible that the parasite's definitive host is one of New Zealand's native bats (Chiroptera), which are known to eat Stenoperla and inhabit streamside forests at some of the localities where parasitised stoneflies were taken. Overall, our results provide further evidence for the importance of sooty mould fungi as a food source for New Zealand insects and highlight the role of Stenoperla as a vector of larval parasites from aquatic to terrestrial hosts.